Project management - Collins, Robert J., 1950- (Construction materials and engineering., 2011)
Project management is the discipline of planning, organising and managing resources to bring about the successful completion of specific project goals and objectives. This book presents current research in the study of project management, including sustainable project management, in building and infrastructure projects.